Problemas de autovalores de Steklov-Neumann e aplicações - Godoi, Juliano Damião Bittencourt de (2012)
In this work we will obtain four main results of existence of weak solution, three of them to elliptic partial di_erential systems with nonlinear boundary conditions and the other to elliptic partial di_erential equations with nonlinear boundary conditions associated with operator p-laplacian. These results will be obtained when there is a kind of interaction among the reaction nonlinearities and the Neumann spectra and an interaction among the boundary nonlinearities and the Steklov spectra, associated with the systems or equations. The tool that we will use is fundamentally based on minimax methods in critical point theory.